Hyper abundant mesopredators and bird extinction in an Atlantic forest island - Galetti,Mauro (2009)
Islands can serve as model systems for understanding how biological invasions affect native species. Here we examine the negative effects of mesopredator mammals on bird richness at Anchieta Island, an 826 ha offshore island in the coast of Brazil. Anchieta Island has the highest density of mammals of the entire Atlantic forest, especially nest predators such as marmosets and coatis, introduced more than 20 years ago. This indiscriminate introduction of mammals may have affected directly the bird community, nowadays represented by 100 species comprised mainly by water-crossing birds, being 73 forest-dwelling species. A small component of these remnant bird species nests in tree holes and on the forest floor, null model analysis suggest that birds within these two nest types are under-represented on Anchieta Island. All guilds were affected negatively, but "opportunist insectivorous/omnivorous". Experiments using artificial nests showed a predation of 73% of nests on the floor while only 26% on the mainland. Camera traps recorded predation by coatis, agoutis, and opossums. The restoration of the bird community on this island is highly constrained by the high density of hyper abundant nest predators.